Technical Efficiency of Microfinance Institutions in Nepal: A Stochastic Frontier Approach - Hakuduwal, Kishor; Nayabhari, Prakash (Swarnadwar, 2025)
This study examines the technical efficiency of microfinance institutions in Nepal. It provides valuable empirical evidence on Nepalese microfinance institutions’ wasted resources and inefficiency. The gross loan portfolio is the output variable, while total assets, cost per borrower, and human resources are input variables. A total of 168 observations from the panel data of 24 microfinance institutions covering the period from 2016/17 AD to 2022/23 AD were analyzed for this study. Data and other necessary information were collected from the audited annual reports of microfinance institutions and the Nepal Rastra Bank. Technical efficiency was calculated using a stochastic frontier model with a production function as the efficiency measure. This study found that total assets, human resources, and cost per borrower significantly influence loans and advances in Nepal’s microfinance institutions. The average technical efficiency of Nepalese microfinance institutions is 77.76 percent. It was also found that microfinance institutions operating for more than 10 years are more efficient than those operating for less than 10 years. Province-level MFIs exhibit the highest technical efficiency compared to national and district-level MFIs. The findings have significant implications for policymakers of microfinance institutions to utilize their resources better and improve efficiency. This study serves as a valuable foundation for increasing the number of microentrepreneurs by minimizing the wasted resources of Nepalese microfinance institutions. The technical efficiency estimates reflect the resource mobilization level of these institutions. This study is distinct from previous research as it is the first to utilize recent panel data of Nepalese microfinance institutions along with the application of the stochastic frontier model.